2014
DOI: 10.1159/000362090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Kidney Disease on Myocardial Blood Flow Regulation in Dogs

Abstract: Background/Aims: Chronic kidney disease (CKD) increases cardiovascular risk possibly due to coronary microvessel dysfunction and impaired myocardial flow reserve. This study investigated the effects of CKD on the regulation and transmural distribution of myocardial blood flow along with oxygen demand during intravenous dobutamine-induced increases in cardiac work. Methods: CKD was produced in dogs by a two-stage subtotal nephrectomy (kidney ablation-infarction model). Serum creatinine and blood urea nitrogen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In the present study dogs developed a kidney disease phenotype corresponding to Stage 2 criteria according to the International Renal Interest Society (IRIS) staging system. In SNx dogs, under normoxemic conditions arterial oxygen content decreased in relation to hematocrit levels; in an earlier study from our laboratory with the same experimental model oxygen extraction levels and distribution of myocardial blood flow were not changed under resting conditions [27]. Those findings supported the concept of a tissue autoregulatory mechanism for oxygen [37,38].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In the present study dogs developed a kidney disease phenotype corresponding to Stage 2 criteria according to the International Renal Interest Society (IRIS) staging system. In SNx dogs, under normoxemic conditions arterial oxygen content decreased in relation to hematocrit levels; in an earlier study from our laboratory with the same experimental model oxygen extraction levels and distribution of myocardial blood flow were not changed under resting conditions [27]. Those findings supported the concept of a tissue autoregulatory mechanism for oxygen [37,38].…”
Section: Discussionsupporting
confidence: 73%
“…We recently documented a marked alteration of coronary vasoregulation and coronary vascular reserve in canines with the renocardiac syndrome phenotype [27]; in these dogs the coronary autoregulatory threshold was more readily exhausted with incremental increases in cardiac work. An overall loss of coronary autoregulation puts the subendocardium at risk of injury and can induce cardiac contractile dysfunction.…”
Section: Effect Of Subtotal Renal Nephrectomy On Cyp450-mediated Metamentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic evaluations of LV geometry were not done in the present study; interestingly heart weight and total LV cross-sectional area were not significantly changed during the experimental timeline but we would expect these results to change with longer durations of prolonged uremia. Body weight, another indicator of renal insufficiency was not measured in this study; however, we [40] and others [9] [41] have reported little variation between control and uremic animals in different species particularly in the early stages (i.e. <6 weeks) after onset of kidney insufficiency.…”
Section: Discussionmentioning
confidence: 75%
“…In 16 dogs, bilateral flank incisions were performed to expose the left and right kidneys. Several dorsal and ventral branches of the left and right renal arteries were ligated to achieve a target of 50-60% infarction of both the kidneys (established by visual verification of topical cyanosis; Kingma et al 2014). In eight of 16 CKD dogs, both kidneys were surgically denervated by cutting all visible nerves of the adventitia of the renal arteries (CKD + RDN group), and then the arteries were moistened with a 20% phenol-ethanol solution for 10-15 min.…”
Section: Surgical Proceduresmentioning
confidence: 99%